The Development of Listening Fun as Learning Media For 11th Grade Students Senior High School (SCHOOLAR: Social and Literature Study in Education, 2025)
Education is important for the children of the nation as it plays a crucial role in shaping their future. English is an international language and one of the subjects taught in schools. Mastery of English involves four essential skills: listening, speaking, reading, and writing. Among these, listening is a critical skill that must be mastered to avoid misunderstandings during communication with English speakers.To address this need, researchers developed a learning medium to help students improve their English language skills. The approach used in this research was Research and Development (R&D). R&D activities are systematic and iterative, forming what is commonly known as the "research and development cycle." The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was applied to develop a learning medium based on a needs analysis.The analysis revealed that Listening Fun (LF) Media was necessary for students to enhance their listening skills. The results of media validation yielded scores of 84% and 96%, indicating that LF Media was suitable for use by students. Similarly, material validation results showed scores of 79% and 83%, further supporting the effectiveness of LF Media. The validation categories for both media and materials were classified as "Very Good." Based on these findings, it was concluded that LF Media is ready to be tested and implemented for student learning.